A neutrophil-mediated carrier regulates tumor stemness by inhibiting autophagy to prevent postoperative triple-negative breast cancer recurrence and metastasis. (June 2022) - Ren, Kebai; He, Jiao; Qiu, Yue; Xu, Zhuping; Wang, Xuhui; Li, Jiaxin; Zang, Shuya; Yang, Yiliang; Li, Jiaxin; Long, Yang; Zhang, Zhirong; Li, Man; et al.
Abstract: Recurrence and metastasis after resection are still the main challenges in clinical treatment of breast cancer. Residual tumor and cancer stem-like cells are the primary culprits of recurrence and metastasis. Recent research studies indicate that autophagy is a cytoprotective mechanism of tumors, which maintains the stemness of cancer cells and promotes tumor proliferation and metastasis. Here, we constructed a "Trojan horse" using neutrophils as the carrier (PH-RL@NEs) to prevent the recurrence and metastasis of postoperative breast cancer. Neutrophils, as a "Trojan horse, " can quickly respond to postoperative inflammation and accurately deliver drugs to the residual tumor site. The inflammation-triggered "Trojan horse" was then opened to release the liposomes containing the chemotherapeutic drug paclitaxel (PTX) and the autophagy inhibitor hydroxychloroquine (HCQ). We found that HCQ could effectively inhibit tumor cell autophagy, interfere with tumor epithelial-mesenchymal transition, and reduce the tumor stem cell-like population. In the orthotopic 4T1 postoperative recurrence models, PTX and HCQ synergistically killed tumors and regulated the stemness of tumor cells, thereby significantly inhibiting tumor recurrence and metastasis. Our work proved that the inhibition of autophagy to reduce tumor stemness is feasible and effective, which opens up a new prospect for postoperative tumor treatment. Statement of significance: The present study aimed to solve the issues of postoperative recurrence and metastasis of breast cancer and low efficiency of drug administration after surgery. For this purpose, we constructed neutrophils containing hydroxychloroquine (HCQ) and paclitaxel (PTX) co-loaded liposomes (PH-RL@NEs), which for the first time regulated the stemness of tumor cells by inhibiting autophagy, thereby inhibiting postoperative recurrence and metastasis of breast cancer cells. The results showed that PH-RL@NEs enhanced the targeted drug delivery efficiency, with the help of postoperative inflammation chemotaxis of neutrophils. HCQ effectively inhibited autophagy of tumor cells and reduced tumor stem cell-like cells, thus improving the therapeutic effect in the 4T1 in situ postoperative recurrence model. Graphical abstract: Image, graphical abstract